2018
DOI: 10.1186/s13048-018-0429-5
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and molecular characterization of a human ovarian clear cell carcinoma cell line (FDOV1)

Abstract: BackgroundOvarian clear cell carcinoma is a distinct histologic subtype with grave survival. The underlying molecular mechanism is not fully elucidated. However, we don’t have many cell lines, which are useful experimental tools for research. We describe the establishment and characterization of a new ovarian clear cell carcinoma cell line from a Chinese patient.ResultsFDOV1 has been subcultured for more than 80 generations. Monolayer cultured cells are polygonal in shape, showing a transparent cytoplasm full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The patient gave written informed consent before surgery according to institutional guidelines in our cancer center (FUSCC 050432-4-1212B). One of the left pelvic lymph nodes was removed during debulking surgery and sent for primary culture; the cells were stably passaged and named FDOVL [ 32 ]. FDOVL cells were cultured in RPMI 1640 medium with 12% fetal bovine serum, 100 IU/mL penicillin, 50 μg/mL streptomycin, 1% sodium pyruvate, 1% HEPES buffer and 1% nonessential amino acids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient gave written informed consent before surgery according to institutional guidelines in our cancer center (FUSCC 050432-4-1212B). One of the left pelvic lymph nodes was removed during debulking surgery and sent for primary culture; the cells were stably passaged and named FDOVL [ 32 ]. FDOVL cells were cultured in RPMI 1640 medium with 12% fetal bovine serum, 100 IU/mL penicillin, 50 μg/mL streptomycin, 1% sodium pyruvate, 1% HEPES buffer and 1% nonessential amino acids.…”
Section: Methodsmentioning
confidence: 99%
“…BRCA1 and NOTCH1 mutations in cells were confirmed by Sanger-sequencing, as described in a previous study [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…And in a further step, a total of 34 established cell lines were used to decode potential therapeutic targets specific for HGSOC [18,19]. In addition, cell lines for ovarian clear cell carcinoma (CCC) [20], low-grade serous ovarian carcinoma (LGSOC) [21], endometrioid adenocarcinoma (EMC) [22], and other pathology were cultured and introduced by researchers worldwide.…”
Section: Conventional Cell Linesmentioning
confidence: 99%
“…39,40 Tumors of some origins such as thyroid, cervical, ovarian, bone and neurologic cancers have not yet well-investigated for this molecular alteration. [39][40][41] Overall, SPOP mutations in gynecological malignancies is not uncommon as some studies found these molecular alterations in 18% of endometrial CCCs 35, 42, 11% of ovarian CCCs 40 , up to 8% of endometrial serous carcinomas 35 and 14% of Müllerian carcinosarcomas 43 . Although functional studies of SPOP in gynecological malignancies are limited, it has been suggested that SPOP mutations can be targeted with DNA damaging agents such as PARP inhibitor as studied in prostate carcinomas.…”
Section: Next Generation Sequencing (Ngs) Characteristicsmentioning
confidence: 99%